Exploration of a scientific career development: case of Kazakhstan - Alibekova, Gulnaz; Amirbekova, Diana; Moldabekova, Aisulu; Zhangaliyeva, Kymbat; Medeni, Tunc (BUKETOV BUSINESS REVIEW, 2025)
The article explores academic career trajectories emphasizing the shifting dynamics between academia and industry. The findings indicate that intrinsic factors, such as motivation and personal aspirations, are complemented by external influences, including financial incentives, mentorship, and institutional support. The use of a quantitative survey was justified by the necessity for statistical analysis of the relationships between career development variables and influencing factors, ensuring empirical rigor. The quantitative approach was complemented by providing a balanced summary representative of the targeted academic population. The study identifies three main dimensions affecting career trajectories: economic and institutional factors, personal and sociocultural motivators, and academic pressures. An understanding of the complex interplay of these factors is crucial for developing supportive policies and practices that accommodate the diverse career aspirations of scholars, fostering an environment capable of sustaining scientific innovation and growth.